Comprehensive numerical modeling of vertical-cavity surface emitting lasers - Corzine, Scott W., author; Scott, J. W., author; Choquette, Kent D., author; Warren, Mial E., author; Lear, Kevin L., author; Hadley, G. Ronald, author; IEEE, publisher (Colorado State University. Libraries, 1996)
We present a comprehensive numerical model for vertical-cavity surface-emitting lasers that includes all major processes affecting cw operation of axisymmetric devices. In particular, our model includes a description of the 2-D transport of electrons and holes through the cladding layers to the quantum well(s), diffusion and recombination of these carriers within the wells, the 2-D transport of heat throughout the device, and a multilateral-mode effective index optical model. The optical gain acquired by photons traversing the quantum wells is computed including the effects of strained band structure and quantum confinement. We employ our model to predict the behavior of higher-order lateral modes in proton-implanted devices and to provide an understanding of index-guiding in devices fabricated using selective oxidation.
Keywords: band structure; carrier mobility; ion implantation; laser cavity resonators; laser modes; quantum well lasers; refractive index; semiconductor device models; surface emitting lasers